Learning Styles of SMPN 1 Students of Dagangan Madiun and Their Implication to English Teaching - Arifin, Zainal; , Agus Wijayanto, Ph.D; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
One of the most difficult set of skills a person could ever struggle to learn is a language. There is no easy way to master a language, particularly a language which is not our first language. In the process of learning a language particularly a second language, there are many variables that determine the success of a language learner which include language learning styles. In a class made up of various learning styles, it is always necessary for the teachers, particularly the language teachers to identify, respect and work on the diversity of the learners' differences. The study investigated the diverse learning styles employed by ESL students in SMPN 1 Dagangan, Madiun Regency, East Java. The students were classified into three levels of competence; high, middle, and low level competence. They were also classified based on gender; males and females. A set of questionnaire was distributed to fifteen students. To get deeper interpretation on their learning styles, the students were also interviewed. The students' learning style preferences were identified based on their levels of competence and gender in order to investigate their differences. The data was analyzed using the case study method and the findings revealed that the students' learning styles can be categorized as visual, auditory, kinesthetic, tactile, individual and group learners. The results of the study indicated that there were some differences in using learning styles by the students of high, middle and low levels of competence. A little difference was also found in male and female students. Thus, it is important for teachers to be aware of their students learning styles.